Clinical Utility and Psychometric Properties of the Traumatic Brain Injury Quality of Life Scale (TBI-QOL) in US Military Service Members. Issue 1 (January 2016) - Lange, Rael T.; Brickell, Tracey A.; Bailie, Jason M.; Tulsky, David S.; French, Louis M.
Abstract : Objective: To examine the clinical utility and psychometric properties of the Traumatic Brain Injury Quality of Life (TBI-QOL) scale in a US military population. Participants: One hundred fifty-two US military service members (age: M = 34.3, SD = 9.4; 89.5% men) prospectively enrolled from the Walter Reed National Military Medical Center and other nationwide community outreach initiatives. Participants included 99 service members who had sustained a mild traumatic brain injury (TBI) and 53 injured or noninjured controls without TBI ( n = 29 and n = 24, respectively). Procedure: Participants completed the TBI-QOL scale and 5 other behavioral measures, on average, 33.8 months postinjury (SD = 37.9). Main Outcome Measures: Fourteen TBI-QOL subscales; Neurobehavioral Symptom Inventory; Posttraumatic Stress Disorder Checklist–Civilian version; Alcohol Use Disorders Identification Test; Combat Exposure Scale. Results: The internal consistency reliability of the TBI-QOL scales ranged from α = .91 to α = .98. The convergent and discriminant validity of the 14 TBI-QOL subscales was high. The mild TBI group had significantly worse scores on 10 of the 14 TBI-QOL subscales than the control group (range, P < .001 to P = .043). Effect sizes ranged from medium to very large ( d = 0.35 to d = 1.13). The largest differences were found on the Cognition-General Concerns ( d = 1.13), Executive Function ( d = 0.94), Grief-Loss ( d = 0.88), Pain Interference ( d = 0.83), and Headache Pain ( d = 0.83) subscales. Conclusion: These results support the use of the TBI-QOL scale as a measure of health-related quality of life in a mild TBI military sample. Additional research is recommended to further evaluate the clinical utility of the TBI-QOL scale in both military and civilian settings.